Novel compound heterozygous of PARKIN causes early-onset Parkinson's disease. (23rd January 2021) - Yu, Li-Hua; Peng, Guo-Ping; Yuan, Yuan; Liu, Xiao-Yan; Ji, Fang; Li, Yi; He, Fang-Ping; Luo, Ben-Yan; Ke, Qing
Highlights: We found a novel form of compound heterozygous mutation in PARKIN, which causes EOPD. The novel form of compound heterozygous mutation consists of c.735−1G > A and Ex2del. Tiny differences in genotypes of PARKIN may lead to huge phenotypic differences. Abstract: Genetics has an essential role in the development of early-onset Parkinson's disease (EOPD). Consequently, genetic screening is of great significance for the diagnosis and treatment of EOPD. In this study, we reported two EOPD with compound heterozygous in PARKIN detected by whole-exome sequencing (WES) and ligation-dependent probe amplification (MLPA). Two unrelated EOPD patients and their parents were enrolled in this study. Genetic analysis was performed through WES and verified by direct Sanger sequencing. In addition, MLPA was used to detect exon dosage. Detailed clinical manifestations and several scale assessments were collected for genotype and phenotype analysis. Compound heterozygous mutations in PARKIN were identified in both patients. c.735−1G > A and Ex2del were detected in Case A, while G284R (c.850 G > C) and Ex2del were found in Case B. These variants were confirmed to originate from their normal parents. The c.735−1G > A is a novel PARKIN variant, which was predicted to result from disappearing of the acceptor splice site by NetGene2. The G284R is a previously reported pathological mutation and the Ex2del is a hot variant of PARKIN found in the Asian population. The phenotypes of both patients are quite different, the main manifestation of case A is rigidity onset, while the case B starts with tremor and foot dystonia. In the present study, we reported a novel compound heterozygous form of PARKIN consisting of splice variant c. 735−1G > A and Ex2del. Moreover, we also found that tiny differences in genotypes of PARKIN may lead to obvious clinical phenotypic differences.